The Effect Of ZnO Mass Variation On Chitosan/ZnO/Cellulose Acetate Composites From Citronella Waste As A Mask Filter Material - Nadia Nadia; Ristika Oktavia Asriza; Adisyahputra Adisyahputra (Jurnal Sains dan Terapan Kimia, 2024)
ABSTRACT Air is an important component that affects human survival, but air quality in Indonesia has greatly decreased due to air pollution. This study used chitosan / ZnO / cellulose acetate composite membranes made from citronella waste as mask filters with ZnO variations of 1%, 2%, and 3%. Composite membranes are made by the phase inversion method and characterized by FTIR, tensile, SEM, and antibacterial tests. Optimum conditions based on the formation of pores measuring 0.17 μm are found in chitosan/ZnO/Cellulose Acetate composite membranes with a  variation of  3%  ZnO. In addition, this variation also has good mechanical properties, with an elongation value of 2.1177% and an elastic modulus of 6.5560 N/m². Based on antibacterial tests, the composite membrane of the 3% ZnO variation also showed the ability to increase antibacterial activity with moderate antibacterial inhibitory strength. Keywords: Composite, Filter Mask, Cellulose Acetate, Chitosan, ZnO